Science and Environmental Communication on YouTube: Strategically Distorted Communications in Online Videos on Climate Change and Climate Engineering - Allgaier, Joachim (Frontiers in Communication, 2019)
The online video-sharing website YouTube is extremely popular globally, also as a tool for information on science and environmental topics. However, only little is known about what kind of information users find when they are searching for information about climate science, climate change and climate engineering on YouTube. This contribution presents results from an exploratory research project that investigates whether videos found on YouTube adhere to or challenge scientific consensus views. Ten search terms were employed to search for and analyze 200 videos about climate and climate modification topics, which are contested topics in online media. The online anonymization tool Tor has been used for the randomization of the sample and to avoid personalization of the results. A heuristic qualitative classification tool was set up to categorize the videos in the sample. 89 videos of the 200 videos in the sample are supporting scientific consensus views about anthropogenic climate change, and climate scientists are discussing climate topics with deniers of climate change in 4 videos in the sample. Unexpectedly, the majority of the videos in the sample (107 videos) supports worldviews that are opposing scientific consensus views: 16 videos deny climate change and 91 videos in the sample propagate straightforward conspiracy theories about climate engineering and climate change. Videos supporting the scientific mainstream view received only slightly more views (16,941,949 views in total) than those opposing the mainstream scientific position (16,939,655 views in total). Consequences for the public communication of climate change and climate engineering are discussed in the second part of the article. The research presented in this contribution is particularly interested in finding out more about strategically distorted communications about climate change and climate engineering in online environments and in critically analyzing them.